STUDIES OF THE PHYTOCHEMISTRY, ANTIOXIDANT AND TYROSINASE INHIBITORY ACTIVITIES OF CANISTEL (POUTERIA CAMPECHIANA (KUNTH.) BAEHNI.) - Nurlaela Fitriansyah, Sani
Exposure of UV light on the skin can induce the reactive oxygen species (ROS), which is called free radical. ROS will cause the accumulation of skin pigment in melanocytes. As a result, the accumulation of ROS in melanocytes will induce the action of tyrosinase which plays a role in the melanin synthesis. Antioxidants can act to scavenge the mechanism of ROS. Pouteria is widely spread in tropical countries. It has been reported that the Pouteria genera contains phenolic and flavonoid groups. Phenolic compounds and flavonoids can act as antioxidant and inhibitor of tyrosinase. Several species of Pouteria have the potential as antioxidant and inhibitor of tyrosinase. One species of Pouteria that has not been widely developed in the pharmaceutical field. In Indonesia is Pouteria campechiana. Several phenolic and flavonoid compounds from P. campechiana have been reported. Based on the closeness in plant systematics, similarities in chemical contents and biological activities can be shown. This research aims to carry out a phytochemical study of P. campechiana guided by antioxidant and tyrosinase inhibitory activities, so that it can be known the extract, fractions and subfractions and active compound with antioxidant and or tyrosinase inhibitory activities from of P. campechiana. This research was started with a preliminary study of antioxidant and tyrosinase inhibitory activity of four plant parts (mesocarps, seeds, twigs and leaves) of P. campechiana). Four plant parts were characterized and extracted by continuous extraction using Soxhlet apparatus with 96% ethanol. The concentrated extract was tested for antioxidant activity by DPPH method and tyrosinase inhibitory activity using L-DOPA as substrate, and total phenolic and determined for flavonoid content. The plant part with the most potent antioxidant and tyrosinase inhibitory activities were further studied. The ethanol leaves extract of P. campechiana had the highest antioxidant (AAI 16.638 ± 0.677), and tyrosinase inhibitory activities IC50 of of 221.16 µg/mL and total phenolic content 18.88 ± 0.08 g GAE/100 g extract. Based on these results, the leaves were subject to further studies. The leaves crude drug was extracted in a series of organic solvents with increasing polarity namely n-hexane, ethyl acetate and ethanol. The three concentrated extracts, n-hexane leaves extract (DN), ethyl acetate leaves extract (DEA) and etanol leaves extract (DE) were monitored by thin layer chromatography (TLC), determined for total phenol and flavonoid content and tested for antioxidant and tyrosinase inhibitory activity. Antioxidant activity of DN, DEA and DE were expressed in antioxidant acivity index (AAI), whose values were 2.320 ± 0.315; 18.94 ± 0.149; 20.345 ± 0.173, respectively, using ascorbic acid, as standards with AAI of 34.562 ± 0.091. Statistically, using on way-ANOVA-post hoc Tukey’s, DEA and DE were not significantly different from ascorbic acid. From the eximination of tyrosinase inhibtion, it was found that DE and DEA were more potent than DN, so DN was not continued for IC50 value. In tyrosinase inhibitory assay the IC50 values of DEA, DE, and the standard kojic acid were 828.54 ± 0.96 µg/mL, 176.55 ± 0.46 µg/mL, and 10.513 ± 0.707, respectively. Based on this data, DEA was further separated through fractionation, subfractionation and purification. Fractionation of the ethyl acetate extract was performed using vaccum liquid chromatography, while subfractionation was done using classical coloumn chromatography and radial chromatography. Selection of fractions and subfractions were based on antioxidant and tyrosinase inhibitory activities. The respective ranges of AAI and IC50 were 0.89-14.50 and 1551.01 –2090.43µg/mL. Based on the results obtained, fraction 5 (F.5) was further subfractionated. The result of subfractionation was obtained 6 combined subfractions namely (SF5.1- SF5.6). Based on activity, SF5.5 was continued to purify, which yielded isolate-1 and isolate-2. The AAI of isolate-1 and isolate-2 were 6.139 ± 0.153 and 8.479 ± 0.187, respectively, while the tyrosinase inhibitory activities of isolate-1 and isolate-2 expressed in % inhibition at a concentration of 1000 µg/mL, were 48.395 ± 0.494 and 47.325± 0.570, respectively. Isolate-1 and isolate-2 were characterized using spectrodensitometry, 1 H-NMR, 13 C-NMR, mass spectroscopy and HPLC. The results confirmed that isolate-1 was quercetin-3-O-rhamnoside (quercitrin) and isolate-2 was quercetin 3-O-glucoside (isoquercitrin).